To Convergence and Beyond? Human Capital, Economic Adjustment and a Return to Growth - FITZGERALD, JOHN (ESRI)
This paper considers the impact on growth and convergence in the EU over the last 20 years of investment in human capital. It examines the current adjustment of a range of economies to the external imbalances at the beginning of the current crisis. Finally it considers how the adjustments under way will contribute to a return to long-term growth.
PUBLISHED
Keywords: growth; human capital; investment